6-2(4-8x)=2(3x-5)

Simple and best practice solution for 6-2(4-8x)=2(3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2(4-8x)=2(3x-5) equation:


Simplifying
6 + -2(4 + -8x) = 2(3x + -5)
6 + (4 * -2 + -8x * -2) = 2(3x + -5)
6 + (-8 + 16x) = 2(3x + -5)

Combine like terms: 6 + -8 = -2
-2 + 16x = 2(3x + -5)

Reorder the terms:
-2 + 16x = 2(-5 + 3x)
-2 + 16x = (-5 * 2 + 3x * 2)
-2 + 16x = (-10 + 6x)

Solving
-2 + 16x = -10 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-2 + 16x + -6x = -10 + 6x + -6x

Combine like terms: 16x + -6x = 10x
-2 + 10x = -10 + 6x + -6x

Combine like terms: 6x + -6x = 0
-2 + 10x = -10 + 0
-2 + 10x = -10

Add '2' to each side of the equation.
-2 + 2 + 10x = -10 + 2

Combine like terms: -2 + 2 = 0
0 + 10x = -10 + 2
10x = -10 + 2

Combine like terms: -10 + 2 = -8
10x = -8

Divide each side by '10'.
x = -0.8

Simplifying
x = -0.8

See similar equations:

| 2.5=d-(20) | | x-(3x+7)=11 | | x-6=-12+2x | | 2.5=d-(.20) | | -9+5x=-5x+1 | | 6.8x-15.3+4.2x=6.4+12x | | b=85+(23)w | | x+8=5x+52 | | 7x+19+-2x=55 | | -3x-5=-47+4x | | 5m-2(4m-1)=-14 | | 10=3x-5x+6 | | x-5-8x=16 | | -14x-4(2x-5)=9 | | -x+6+2x=13 | | 18=8-6b | | (30+5x)+(10x+15)=180 | | (x+6)(3x+8)=0 | | -1-5x+3x=1 | | y-5-2=10 | | 12x-13+8=2x | | 4=x+x+2 | | 12x+4-26=-2(3x-82) | | 2y-6x-4=0 | | 10w+5-3w=40 | | 7x-(2x-12)=-8 | | 25x=10-3+5x | | 5(x+2)-(3x-8)= | | 6+(n+4)+(n+4)=51 | | 6+(n+2)+(n+4)=51 | | n+(n+2)+(n+4)=51 | | 8x=240 |

Equations solver categories